METHODOLOGICAL APPROACHES TO THE ASSESSMENT OF ENVIRONMENTAL RISKS FROM SOLID DOMESTIC WASTE LANDFILLS - KORBUT, MARIIA; SAFRANOV, TAMERLAN; MALOVANYY, MYROSLAV (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The paper presents the results of research on the topical problem of assessing the environmental risk from the functioning of solid waste landfills on the territory of Ukraine. The accumulation of solid waste in landfills and landfills causes pollution of the atmosphere, surface and underground waters, fertile soils, negatively affects natural ecosystems, harms agriculture, and greenhouse gas emissions affect climate change. Environmental risk is the potential probability of negative impact on the environment as a result of various anthropogenic or natural processes. Qualitative and quantitative methods for assessing environmental risks are analysed. Methodical approaches to the assessment of environmental risks from solid waste landfills have been formed and substantiated, the concept of risk has been structured and the most dangerous (in terms of social and environmental consequences) hazardous situations and indicators of the level of danger of landfills and solid waste landfills for adjacent territories have been studied. It is substantiated that the integrated risk should be considered as a complex indicator of security, expressed in a single cost equivalent, which combines risks of a social, material nature and environmental damage.
Keywords: solid waste landfill; environmental risk; risk assessment; waste